Pengaruh Kepemimpinan, Kerjasama dan Disiplin Kerja terhadap Kinerja Pegawai pada PT. Perkebunan Nusantara IV Kota Medan - Tivana Putri Sahira; Fitra Arlina Nasution; Saimara A.M Sebayang (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research was conducted at PTPN IV Medan with the aim of research to analyse the effect of leadership, cooperation, and work discipline partially and simultaneously on employee performance in the company. The population is employees who work in the company as many as 257 people, the sample used is a random sample with sampling using the Slovin formula, so that the number of research samples obtained is 72 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature study, survey and observation. The data analysis technique is multiple linear regression, classical assumption test and hypothesis testing. The results showed that leadership, cooperation and work discipline partially and simultaneously had a positive and significant effect on employee performance at PTPN IV Medan. There is a sufficient correlation between leadership, cooperation and work discipline with employee performance and the percentage of 29.1% and the remaining 70.9% can be explained by other variables not studied such as compensation, incentives, training, promotions and so on.